Exploring Learner Autonomy in AI-Assisted EFL Learning: A Comparative Classroom Observation of ChatGPT Use in Indonesian Senior High Schools - Meta Keumala; Zaiyana Putri; Nyak Mutia Ismail; Cut Faizah; Cut Mulia Zuhra (English Department, Universitas Negeri Surabaya, 2026)
The rapid integration of artificial intelligence (AI) into English as a Foreign Language (EFL) learning has shifted attention from technological utility to the enactment of learner autonomy. This study describes and compares how senior high school students demonstrate autonomous learning behaviours when using ChatGPT in English classrooms. Employing a qualitative descriptive design with a comparative classroom observation strategy, the study was conducted at SMA 3, SMA 4, and SMA 5 Banda Aceh. Data were collected using an observation sheet covering ten indicators of learner autonomy and analysed through a four-point rubric. The findings showed noticeable differences across the three schools. SMA 3 demonstrated the highest autonomy level (82.5%), characterised by initiative, goal setting, persistence, and metacognitive awareness. SMA 4 showed a moderate level (55%), with students displaying persistence and feature exploration but remaining dependent on teacher instruction. SMA 5 showed the lowest level (37.5%), with students appearing passive, hesitant, and limited in independent reflection. The findings suggest that ChatGPT may create opportunities for independent language practice, but autonomy does not emerge automatically. Pedagogical guidance remains necessary to help students move from teacher-dependent AI use toward strategic, reflective, and self-regulated learning.